Pelatihan kewirausahaan untuk meningkatkan ekonomi keluarga pada kader kesehatan - Khasanah, Aulia Uswatun; Wibowo, Frendy; Utomo, Fahman Hadi (Nur Science Institute, 2025)
This community service program aimed to improve family economic resilience by providing entrepreneurship training for health cadres under Pimpinan Daerah ‘Aisyiyah (PDA) Surakarta. Many health cadres face financial challenges due to the limited incentives for voluntary work, which affects their ability to sustain community health roles. The program introduced low-capital business models such as reseller and dropshipping, combined with digital marketing strategies through Instagram. The activity involved 65 participants and utilized participatory methods, including lectures, interactive discussions, and practical sessions. Results showed a significant increase in participants’ understanding of entrepreneurship concepts and digital marketing skills. More than 85% of participants successfully created Instagram business accounts and promotional content following the training. This program demonstrates that digital-based entrepreneurship training effectively empowers health cadres, enhances their economic independence, and contributes to sustainable family welfare.